Efektivitas Pembelajaran Berdiferensiasi Dalam Meningkatkan Keterampilan Menulis Teks Deskripsi Siswa Kelas VII SMP Negeri 2 Ranah Pesisir - Riska Mayeni; Dina Fitria Handayani; Revi Handayani (Kilau Publishing, 2026)
This study aims to analyze the effectiveness of differentiated instruction in improving the descriptive text writing skills of seventh-grade students at SMP Negeri 2 Ranah Pesisir. The research employed a quantitative approach using a quasi-experimental method with a pretest–posttest control group design. The sample consisted of two classes: an experimental class of 30 students who received differentiated instruction and a control class of 30 students who received conventional instruction. Data were collected through descriptive text writing tests administered before (pretest) and after (posttest) the treatment. The research instrument was a writing test assessed based on five aspects: content, organization, language use, vocabulary, and writing mechanics. The data were analyzed using prerequisite tests, including normality and homogeneity tests, followed by an independent samples t-test to determine differences in learning outcomes between the two groups. The findings revealed that both groups showed improvements in descriptive writing skills. In the experimental group, the mean score increased from 67.30 in the pretest to 84.60 in the posttest, representing an improvement of 17.30 points. Furthermore, the results of the paired samples t-test indicated a significance value of 0.000 (p < 0.05), demonstrating a statistically significant difference in students' writing skills before and after the implementation of differentiated instruction. These findings indicate that differentiated instruction is effective in improving students' descriptive text writing skills because it accommodates differences in students' learning readiness, interests, and learning profiles, thereby creating a more active, meaningful, and student-centered learning process. Therefore, differentiated instruction can serve as an effective alternative strategy in Indonesian language teaching to enhance junior high school students' writing skills.